Impact of Varied Lead Concentrations on Lead Accumulation in the Body, Heart and Gill Damage of Milkfish (Chanos chanos) - Sukardi, Reski Wahyuni; Djawad, Muhammad Iqbal; Azis, Hasni Yulianti; Manaf, Sharifah Raina (Marine Science Department Diponegoro University, 2024)
Milkfish (Chanos chanos) is valued in aquaculture for its affordability and nutritional richness. However, conventional farming techniques frequently result in suboptimal yields due to lead (Pb) contamination. Traditional milkfish ponds are typically situated near coastal areas, river waters, estuaries, ports, and industrial zones, rendering them susceptible to contamination, particularly from heavy metals, like Pb. This study aimed to analyze Pb accumulation in the body of milkfish juvenile, identify liver and gills damage, and examine the growth rate and survival of milkfish exposed to Pb at various concentrations. Juvenile milkfish were exposed to various concentrations of PbNO3, namely 0 mL.L-1, 0.08 mL.L-1, 0.8 mL.L-1, and 8 mL.L-1, including the non-exposed control group. The metal content of the fish bodies was measured using an AA spectrophotometer. Histological analysis of the liver and gills of the fish was performed to evaluate organ damage. The results showed significant Pb accumulation has been observed in milkfish exposed to high Pb concentrations. The control treatments showed a decrease in metal content, whereas treatments with high concentrations showed a significant increase. Exposure to Pb within 30 d can cause organ damage, such as inflammatory cells, secondary lamella fusion, and necrosis that occurs in the gills. In the liver, there is damage such as the accumulation of inflammatory cells, necrosis, and hydrofic degeneration. Pb exposure rapidly damages and disrupts milkfish's biological functions, influencing survival and growth. Pb exposure with doses 8 mL.L-1 significantly affected juvenile milkfish within approximately 60 min.